Candida albicans SET3 Plays a Role in Early Biofilm Formation, Interaction With Pseudomonas aeruginosa and Virulence in Caenorhabditis elegans - Fourie, Ruan; Albertyn, Jacobus; Sebolai, Olihile; Gcilitshana, Onele; Pohl, Carolina H. (Frontiers in Cellular and Infection Microbiology, 2021)
The yeast Candida albicans exhibits multiple morphologies dependent on environmental cues. Candida albicans biofilms are frequently polymicrobial, enabling interspecies interaction through proximity and contact. The interaction between C. albicans and the bacterium, Pseudomonas aeruginosa, is antagonistic in vitro, with P. aeruginosa repressing the yeast-to-hyphal switch in C. albicans. Previous transcriptional analysis of C. albicans in polymicrobial biofilms with P. aeruginosa revealed upregulation of genes involved in regulation of morphology and biofilm formation, including SET3, a component of the Set3/Hos2 histone deacetylase complex (Set3C). This prompted the question regarding the involvement of SET3 in the interaction between C. albicans and P. aeruginosa, both in vitro and in vivo. We found that SET3 may influence early biofilm formation by C. albicans and the interaction between C. albicans and P. aeruginosa. In addition, although deletion of SET3 did not alter the morphology of C. albicans in the presence of P. aeruginosa, it did cause a reduction in virulence in a Caenorhabditis elegans infection model, even in the presence of P. aeruginosa.